THE APPLICATION OF VOA SPECIAL ENGLISH TO TEACH LISTENING SKILL TO 11TH FORM STUDENTS IN AN DUONG HIGH SCHOOL - Nguyễn, Thị Hoài Phương (2020)
This study was conducted with the attempt to raise the awareness and provide both English teachers and 11th form students in An Duong High school a valueable sourse, VOA special English, for teaching and learning English, especially listening skill. During the process of carrying out the study, 50 students and 2 English teachers have got involved in the study with their great responsibility for taking part in the VOA listening classes and answering questionnaires as well as interview in order to help the researcher finishing the survey hopefully.After data analysis process, significant findings were noticeable. It seems that exploitation of authentic materials, particularly VOA special English in teaching and learning at An Duong High school still remained unfamiliar with both English teachers and students. From what revealed through the survey, it is recommended that teachers, students as well as the educational administrators in An Duong High school should change their thought about what for and how to learn English so that learning English can be more communicative.